2018
DOI: 10.3389/fphys.2018.01845
|View full text |Cite
|
Sign up to set email alerts
|

The Case Study of Nesfatin-1 in the Pancreas of Tursiops truncatus

Abstract: Nesfatin-1 (Nesf-1) is an anorexigenic peptide involved in the regulation of homeostatic feeding. Nesf-1 is expressed in the central nervous system and other organs, including pancreas, where it promotes the release of insulin from β-cells. This raises the possibility that Nesf-1 dysfunction could be involved in metabolic disorders, particularly in type 2 diabetes mellitus (T2D). Recently, it has been discovered that dolphins can be a natural animal model that fully replicates human T2D, due to its prolonged g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…It is likely that resistin action is affected by the participation of other molecules, as is the case for insulin, whose action is modulated by glucagon, nesfatin, leptin and resistin. [29][30][31][32] This immunohistochemical study identified resistin positive cells in the uterus of sheep, supporting the existence of a peripheral resistin system also in the reproductive apparatus of this animal species. There are no previous studies in this species on the resistin WB identification.…”
Section: Discussionsupporting
confidence: 70%
“…It is likely that resistin action is affected by the participation of other molecules, as is the case for insulin, whose action is modulated by glucagon, nesfatin, leptin and resistin. [29][30][31][32] This immunohistochemical study identified resistin positive cells in the uterus of sheep, supporting the existence of a peripheral resistin system also in the reproductive apparatus of this animal species. There are no previous studies in this species on the resistin WB identification.…”
Section: Discussionsupporting
confidence: 70%
“…Third, nesfatin-1 and its related inflammatory factors may play a role in the pathogenesis of impaired cognitive function in T2DM, which needs to be confirmed by further studies. Additionally, considering that nesfatin-1 is an anorexigenic peptide involved in the regulation of homeostatic feeding 68 and HbA1c levels, glucose metabolism indices, and inflammation markers could be affected by dietary interventions, [69][70][71] dietary intervention may be a possible strategy to improve the cognitive function of T2DM patients as it affects the indicators mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of each immunohistochemical reaction was checked in repeated trials via pre-absorption of primary antibody Nesf-1 (H-003-24; Phoenix Pharmaceuticals) with homologous antigen Nesf-1 (1-45)/Nesf-1, N-terminal (Human) (003-24; Phoenix pharmaceuticals) (up to 50 mg/mL antiserum in the final dilution). Positive controls were made by sections of rat testis [10]. Internal reaction controls were carried out by substituting primary antisera or secondary antisera with 1× PBS or normal serum in the specific step.…”
Section: Controls Of Specificitymentioning
confidence: 99%
“…However, the use of anti-Nesf-1 antibodies is not enough to inhibit the sense of satiety induced by leptin: therefore, Nesf-1 is an anorexigenic molecule with a leptin-independent action in mammals [7]. As with many other central appetite regulators, NUCB2/Nesf-1 was also detected in peripheral tissues in different vertebrate models that had an important role in energy homeostasis, such as adipose tissue [8], pancreas [9,10], and in middle and lower segments of gastric mucosal glands [11], as well as in the submucosal layer of the duodenum [9]. Stengel and colleagues described NUCB2/Nesf-1 in the gastric X/A-like endocrine cells of the stomach and showed co-localization with the orexigenic hormone ghrelin in mammals.…”
Section: Introductionmentioning
confidence: 99%